2018
DOI: 10.1002/ccd.27825
|View full text |Cite
|
Sign up to set email alerts
|

MAGnesium‐based bioresorbable scaffold and vasomotor function in patients with acute ST segment elevation myocardial infarction: The MAGSTEMI trial: Rationale and design

Abstract: This trial will shed light on the vascular vasomotion following BRS implantation in the complex scenario of STEMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
(46 reference statements)
1
5
0
Order By: Relevance
“…Nevertheless, despite these encouraging findings, caution is strongly needed when interpreting data coming from a small, single-arm study with limited follow-up. The ongoing prospective Italian multicenter SHERPA-MAGIC (NCT03327961) registry, as well as other ongoing projects MAGSTEMI (NCT03234348) [25] and SOLVE-ACS (NCT03773081) will hopefully confirm and expand these preliminary findings. Larger randomized controlled studies and longer-term follow-up are needed to deeply understand the potential benefits associated with the implantation of the RMS in AMI patients.…”
supporting
confidence: 52%
“…Nevertheless, despite these encouraging findings, caution is strongly needed when interpreting data coming from a small, single-arm study with limited follow-up. The ongoing prospective Italian multicenter SHERPA-MAGIC (NCT03327961) registry, as well as other ongoing projects MAGSTEMI (NCT03234348) [25] and SOLVE-ACS (NCT03773081) will hopefully confirm and expand these preliminary findings. Larger randomized controlled studies and longer-term follow-up are needed to deeply understand the potential benefits associated with the implantation of the RMS in AMI patients.…”
supporting
confidence: 52%
“…BVS in humans are reported to resorb within three to five years whilst theoretically liberating the artery of the "cage", reducing physiological shear stress and restoring pulsatility, cyclical strain and mechano-transduction (108). These have been associated with late scaffold thrombosis and other complications that have led to it being licensed for research purposes only (109,110). Drug Coated Balloon Angioplasty is a method currently widely used to treat ISR that has been proposed as a technique that does not carry the same level of risk of ST or prolonged, mandated anti platelet therapy given its absence of scaffold structure (104,(111)(112)(113).…”
Section: The Effect Of Percutaneous Coronary Intervention On Endothelial Functionmentioning
confidence: 99%
“…There have been various studies looking into the effects of PCI on endothelial function given that intuitively, the presence of the stents have an effect on the coronary artery endothelium and vasomotion (see Table 3) (14). A mechanism of stent thrombosis includes the presence of the scaffold not only causing local inflammatory effects but also attenuating endogenous vessel NO levels increasing thrombogenicity of the treated segment (109). The Caramori study (115) showed vasoconstriction in BMS at the maximal doses of acetylcholine administered, which was at a much high concentration than used in the other studies looking at endothelial dysfunction where vasoconstrictor responses were demonstrated in DES at lower doses.…”
Section: The Effect Of Percutaneous Coronary Intervention On Endothelial Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, other BRS with differing designs and drugs are still available on the market for use in clinical studies. One of these -a magnesium-based BRS -is currently being tested in ST-segment elevation myocardial infarction (STEMI), where their physiological advantages, such as late lumen enlargement and vasomotion, appear particularly appealing 6,7 . Previous studies on BRS in STEMI have shown contrasting results with either a noninferior vascular healing response with a low rate of events or a higher rate of early device thrombosis at one-year follow-up 8,9 .…”
Section: Introductionmentioning
confidence: 99%